ANALYSIS OF MEDIA REPORT FRAMING ON JOKOWI DYNASTY POLITICS IN THE 2024 PRESIDENTIAL ELECTION - Moch. Rifqi Mei Redha; Suswanta Suswanta; Ridho Al-Hamdi (Universitas Negeri Semarang, 2024)
The issue of the Jokowi political dynasty is a trending topic in the 2024 presidential election. Media reporting tends to lead to negative reporting, so researchers differentiate between positive, neutral, and negative framing from the various sources selected. This research aims to look at media framing in providing a view of the politics of the Jokowi dynasty in the 2024 presidential election. The method used is a literature review analysis approach with data sources from news media Antara.news, Kompas.com, and Suara.com. The analysis tools used in this research are Vosviewers and Nvivo 12 Plus. This study found that President Jokowi also provided support to his sons Gibran Rakabuming Raka and Anwar Usman, as chairman of the Constitutional Court (MK), was proven to have violated ethics by giving a decision regarding the age limit for candidacy. This can be the basis for future research in building perspectives and uncovering complexities.